Some Notes on Groundwater As A Domestic Water Supply of The Yogyakarta Municipality - Sudarmadji . (Indonesian Journal of Geography, 1994)
Water supply in Yogyakarta municipality is mainly originated from two main sources, the pipe water and groundwater. The pipe water which is operated by the local drinking water authority does not suffice for the water demand of the people in the city. Tire second source is groundwater, which is used by most people in the city by traditional system. The aquifer of the Yogyakarta which consists of volcanic materials erupted by Merapi volcano is fairly good, however the expansion of the city area toward the northern and north eastern area may reduce groundwater recharge. The rapid growth of population and other city facilities such as hotels may cause groundwater supply to decline. Groundwater quality in certain area may subject to pollution by domestic wastes, assigned by the high content of chemical substances such as iron and sulphate, besides high content of coliform bacteria, and nitrite. Heavy metals were undetected in the groundwater of the area